P132 Informed decision or 'formed decision': are we giving choice to patients to choose definitive management of malignant pleural effusion? A retrospective cohort study. (11th November 2022) - Iqbal, B; Denniston, P; Addala, D; Bedawi, E; Hallifax, R; Sundralingam, A; Wrightson, J; Rahman, NM
Abstract : Introduction and Objectives: For definitive management of malignant pleural effusion (MPE), chest drain with talc pleurodesis (TP) and indwelling pleural catheter (IPC) are commonly used with no proven superiority of one modality over the other in symptom control. 1 IPCs are increasingly used, but it is not clear if this is always an informed, patient-based decision or more guided by medical advice. This study aimed to assess how often this was a clear, information-based patient choice and to elucidate reasons for preferred treatment. Methods: We collected retrospective data of all patients who received definitive treatment for MPE (TP or IPC) between May 2021 to May 2022, in a tertiary pleural centre in the UK. We reviewed the medical records to assess baseline characteristics, documentation of options discussed and identified reasons influencing choices. Results: 97 procedures were performed for definitive management of MPE out of 546 total pleural procedures. Of this, 82/97 patients were treated with IPC and 15 with TP. In the IPC group, 41/82 were male (mean age 73.1 years) and 41 were female (mean age 69.9 years). 60(73%) had documented discussion of options, 9(11%) had no documentation and the discussion was unclear in 13(15%). 52(63%) were eligible for both treatments; of these, 36/52(69%) had options discussed and the precise reasons for IPC choice were documented in 28(53%) ( figure 1a ). In the talc pleurodesis group, 10/15 were male (mean age 78.2 years) and 5 were female (mean age 75.2 years). All patients were eligible for either IPC or talc; 10(66%) had discussion of options and precise reasons for talc choice were documented in 8(53%) ( figure 1b ). Overall, 67/97(69%) cases had both choices for definitive MPE treatments, 46(68%) had documentation of options discussed and 36(53%) had precise choices documented. Conclusion: About 1/3rd of patients who have the choice of either TP or IPC to manage MPE are either not having detailed discussions or need to have clearer documentation. We propose standardised documentation format for all MPE patients to improve shared decision making. References: Bibby AC, et al . ERS/EACTS statement on the management of MPE. 2019. ERJ .